Pathogen suppression by microbial volatile organic compounds in soils. Issue 8 (2nd July 2019) - de Boer, Wietse; Li, Xiaogang; Meisner, Annelein; Garbeva, Paolina
ABSTRACT: There is increasing evidence that microbial volatile organic compounds (mVOCs) play an important role in interactions between microbes in soils. In this minireview, we zoom in on the possible role of mVOCs in the suppression of plant-pathogenic soil fungi. In particular, we have screened the literature to see what the actual evidence is that mVOCs in soil atmospheres can contribute to pathogen suppression. Furthermore, we discuss biotic and abiotic factors that influence the production of suppressive mVOCs in soils. Since microbes producing mVOCs in soils are part of microbial communities, community ecological aspects such as diversity and assembly play an important role in the composition of produced mVOC blends. These aspects have not received much attention so far. In addition, the fluctuating abiotic conditions in soils, such as changing moisture contents, influence mVOC production and activity. The biotic and abiotic complexity of the soil environment hampers the extrapolation of the production and suppressing activity of mVOCs by microbial isolates on artificial growth media. Yet, several pathogen suppressive mVOCs produced by pure cultures do also occur in soil atmospheres. Therefore, an integration of lab and field studies on the production of mVOCs is needed to understand and predict the composition and dynamics of mVOCs in soil atmospheres. This knowledge, together with the knowledge of the chemistry and physical behaviour of mVOCs in soils, forms the basis for the development of sustainable management strategies to enhance the natural control of soil-borne pathogens with mVOCs. Possibilities for the mVOC-based control of soil-borne pathogens are discussed. Abstract : The authors review literature reporting on pathogen suppressive activities of volatiles (mVOCs) produced in soils by microbial communities and indicate management strategies to enhance mVOC-mediated disease control.